2009
DOI: 10.1002/jcp.21971
|View full text |Cite
|
Sign up to set email alerts
|

Direct cell–cell contact between periodontal ligament fibroblasts and osteoclast precursors synergistically increases the expression of genes related to osteoclastogenesis

Abstract: The formation of bone resorbing osteoclasts in vivo is orchestrated by cells of the osteoblast lineage such as periodontal ligament fibroblasts that provide the proper signals to osteoclast precursors. Although the requirement of cell-cell interactions is widely acknowledged, it is unknown whether these interactions influence the expression of genes required for osteoclastogenesis and the ultimate formation of osteoclasts. In the present study we investigated the effect of cell-cell interaction on the mRNA exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
74
1
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 87 publications
(93 citation statements)
references
References 32 publications
15
74
1
3
Order By: Relevance
“…No previous reports have described the effects of osteoclasts on fibroblasts, but studies have found that fibroblasts can induce differentiation of precursor cells into mature osteoclasts. Bloemen and colleagues (9) found that gene expression of intercellular adhesion molecule-1 (ICAM-1) and osteoclastogenesis-related genes (RANKL, RANK, TNF-a, and IL-1b) was highly up-regulated in co-cultures with fibroblasts. The current study has shown that conditioned medium of osteoclastlike cells can influence the adhesion molecule pathway of fibroblasts.…”
Section: Mirna Microarray Data Analysismentioning
confidence: 99%
“…No previous reports have described the effects of osteoclasts on fibroblasts, but studies have found that fibroblasts can induce differentiation of precursor cells into mature osteoclasts. Bloemen and colleagues (9) found that gene expression of intercellular adhesion molecule-1 (ICAM-1) and osteoclastogenesis-related genes (RANKL, RANK, TNF-a, and IL-1b) was highly up-regulated in co-cultures with fibroblasts. The current study has shown that conditioned medium of osteoclastlike cells can influence the adhesion molecule pathway of fibroblasts.…”
Section: Mirna Microarray Data Analysismentioning
confidence: 99%
“…It is well known that bone homeostasis is a dynamic balance that is maintained by bone formation and bone resorption [1,2]. Osteoclasts, which develop from hematopoietic osteoclast precursors, are the principle cells responsible for bone resorption [3].…”
Section: Introductionmentioning
confidence: 99%
“…In RAW 264.7 osteoclastic cells, PTEN overexpression antagonizes RANKL-stimulated osteoclast survival and osteopontin-stimulated cell migration [Sugatani et al, 2003]. ICAM1, which encodes a glycoprotein that binds to several integrin classes, is important in osteoclastogenesis [Kurachi et al, 1993;Okada et al, 2002;Garcia-Palacios et al, 2007;Bloemen et al, 2010]. Thus, the currently observed stimulatory effect of testosterone on ICAM1 is paradoxical, and merits further investigation as to its physiological or pathophysiological significance.…”
Section: Discussionmentioning
confidence: 80%